Exogenous Shocks and Business Process Management - Maximilian Röglinger; Ralf Plattfaut; Vincent Borghoff; Georgi Kerpedzhiev; Jörg Becker; Daniel Beverungen; Jan vom Brocke; Amy Van Looy; Adela del-Río-Ortega; Stefanie Rinderle-Ma; Michael Rosemann; Flavia Maria Santoro; et al. (Business & Information Systems Engineering, 2022)
Business process management (BPM) drives corporate success through effective and efficient processes. In recent decades, knowledge has been accumulated regarding the identification, discovery, analysis, design, implementation, and monitoring of business processes. This includes methods and tools for tackling various kinds of process change such as continuous process improvement, process reengineering, process innovation, and process drift. However, exogenous shocks, which lead to unintentional and radical process change, have been neglected in BPM research although they severely affect an organization's context, strategy, and business processes. This research note conceptualizes the interplay of exogenous shocks and BPM in terms of the effects that such shocks can have on organizations' overall process performance over time. On this foundation, related challenges and opportunities for BPM via several rounds of idea generation and consolidation within a diverse team of BPM scholars are identified. The paper discusses findings in light of extant literature from BPM and related disciplines, as well as present avenues for future (BPM) research to invigorate the academic discourse on the topic.
Keywords: 000; Business process management; Exogenous shocks; Challenges; Opportunities